2014
DOI: 10.1016/j.cell.2014.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute-Bound Small RNAs from Promoter-Proximal RNA Polymerase II

Abstract: Argonaute (Ago) proteins mediate post-transcriptional gene repression by binding guide microRNAs (miRNAs) to regulate targeted RNAs. To confidently assess Ago-bound small RNAs, we adapted a mouse embryonic stem cell system to express a single epitope-tagged Ago protein family member in an inducible manner. Here, we report the small RNA profile of Ago-deficient cells and show that Ago-dependent stability is a common feature of mammalian miRNAs. Using this criteria and immunopurification, we identified a new Ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
133
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 63 publications
7
133
1
Order By: Relevance
“…Due to decreases in expression levels of AGO2 mRNA in old PBMCs implicate a change in miRNA abundance as observed in mouse embryonic fibroblasts lacking AGO2 (Zamudio Jesse, Kelly Timothy & Sharp Phillip, 2014). In order to test whether the reduction of AGO2 expression due to differences in m6A modification leads to the reduction of mature miRNA level during aging, we performed miRNA microarray analysis of the young and old PBMCs.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to decreases in expression levels of AGO2 mRNA in old PBMCs implicate a change in miRNA abundance as observed in mouse embryonic fibroblasts lacking AGO2 (Zamudio Jesse, Kelly Timothy & Sharp Phillip, 2014). In order to test whether the reduction of AGO2 expression due to differences in m6A modification leads to the reduction of mature miRNA level during aging, we performed miRNA microarray analysis of the young and old PBMCs.…”
Section: Resultsmentioning
confidence: 97%
“…This suggests that there are other key factors that modulate specific miRNA abundance. AGO2 is an ideal protein to modulate miRNA abundance in cellular senescence and aging since its association with mature miRNAs prevents them from degradation without affecting canonical miRNA processing (Zamudio Jesse et al., 2014). …”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if similar dynamics affect termination by eukaryotic RNAPII, but RNA secondary structures have also been proposed to aid RNAPII termination (63,64), including effects of bacterial intrinsic terminators in yeast RNAPII (8) and the HIV-1 TAR hairpin on human RNAPII (65). Alterations of the TL in yeast RNAPIII also affect TE (66), and the presence of the TL in archaeal RNAP prevents aberrant termination (67).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has indicated that human AGO proteins can regulate splicing through modulating chromatin structure (9,10) and can promote gene repression in cis by localizing to nascent tRNA (11). Thus, RNAi-mediated control of gene expression exists also in vertebrate cells but functions in mechanisms distinct from those within the cytoplasm (12,13). Despite these reports demonstrating a role for RNAi in regulating the chromatin structure of vertebrates, similar studies have shown that the loss of the RNAi machinery impacts chromatin structure indirectly through miRNA biogenesis and post-transcriptional gene regulation (14).…”
mentioning
confidence: 99%